Primary gastric choriocarcinoma: A case report and review of the literature - Murat GÜRSOY; Gürden GÜR; Yücel ÜSTÜNDAĞ; Beyhan DEMİRHAN; Çağlar BAYSAL; Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-